The cat stole my pants - Pastis, Stephan (Pastis, Stephan. Timmy Failure, 2019)
Timmy Failure, the world's greatest detective, is in Key West, Florida--but he is definitely not on vacation with his mother and Doorman Dave, who he insists never even got married. No, he is there on a job, but his business partner has abandoned him, fleeing to Cuba for political asylum--all Timmy has is an unpaid intern to help him find buried treasure.